CENTRAL BANK DIGITAL CURRENCY (CBDC) DAN TRANSFORMASI SISTEM MONETER INTERNASIONAL: SYSTEMATIC LITERATURE REVIEW PERIODE 2020–2025 - Anastasia D'Ornay; Ades Asike (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
The transformation of the digital economy has accelerated the development of digital currency, particularly Central Bank Digital Currency (CBDC), as an innovation with the potential to reshape the architecture of the international monetary system. The rapid growth of research on this topic has generated diverse and fragmented findings, requiring a comprehensive synthesis to achieve a more holistic understanding. This study aims to conduct a Systematic Literature Review (SLR) to identify research trends, analyze the implications of digital currency for the international monetary system, evaluate the theoretical and methodological approaches employed, and identify research gaps and future research agendas. This SLR follows the PRISMA 2020 guidelines by searching literature databases including Scopus, Web of Science, ScienceDirect, SpringerLink, Emerald Insight, Wiley Online Library, Taylor & Francis Online, IEEE Xplore, and Google Scholar. Articles were selected based on predetermined inclusion and exclusion criteria, resulting in 42 articles that were analyzed using thematic analysis and narrative synthesis approaches. The review findings indicate that research on digital currency is predominantly focused on Central Bank Digital Currency (CBDC), monetary policy, cross-border payment systems, financial stability, and digital financial regulation. The synthesis further reveals that digital currency has the potential to enhance payment efficiency and support the transformation of the monetary system; however, its implementation continues to face challenges related to interoperability, cybersecurity, data protection, and international regulatory harmonization. Furthermore, the literature remains dominated by conceptual studies and research focusing on developed countries, while cross-country empirical investigations and long-term impact evaluations remain limited. This study concludes that digital currency represents a strategic element in the evolution of the international monetary system and requires multidisciplinary approaches and global policy collaboration. The findings contribute to theoretical development, provide directions for future research, and offer an evidence-based foundation for central banks and policymakers in designing secure, inclusive, and sustainable digital currency ecosystems.